Praktik Jurnalisme Lingkungan oleh Harian Jawa Pos - Putri Aisyiyah Rachma Dewi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2011)
The main responsibility of environmental journalism is to ensure that the mass media as the primary source of public information do its duty to publish their environmental issues so the public can clearly understand and realize the condition of their environment. When there is an environmental issue, either natural disasters and environmental damage caused by human activities, media is also required to have foresight in focusing on the main cause of the disasters, environmental mitigation, and rehabilitation that can be pursued. By taking the case of published investigation of Jawa Pos about the environmental disasters of hot mud flow in Brantas Block, East Java, this article explores how the practice of environmental news coverage should be done by the mass media in Indonesia. Using the methods of textual analysis, the author tries to gain an insight of how the Jawa Pos journalists comprehend and process the news of the hot mud flow.